Reinforcing styrene butadiene rubber with lignin-novolac epoxy resin networks - P. Yu; H. He; C. Jiang; D. Wang; Y. Jia; L. Zhou; D. M. Jia (eXPRESS Polymer Letters)
In this study, lignin-novolac epoxy resin networks were fabricated in the styrene butadiene rubber (SBR) matrix by combination of latex compounding and melt mixing. Firstly, SBR/lignin compounds were co-coagulated by SBR latex and lignin aqueous solution. Then the novolac epoxy resin (F51) was added in the SBR/lignin compounds by melt compounding method. F51 was directly cured by lignin via the ring-opening reaction of epoxy groups of F51 and OH groups (or COOH groups) of lignin during the curing process of rubber compounds, as was particularly evident from Fourier transform infrared spectroscopy (FTIR) studies and maximum torque of the curing analysis. The existence of lignin-F51 networks were also detected by scanning electron microscope (SEM) and dynamic mechanical analysis (DMA). The structure of the SBR/lignin/F51 was also characterized by rubber process analyzer (RPA), thermogravimetric analysis (TGA) and determination of crosslinking density. Due to rigid lignin-F51 networks achieved in SBR/lignin/F51 composites, it was found that the hardness, modulus, tear strength, crosslinking density, the temperature of 5 and 10% weight-loss were significantly enhanced with the loading of F51.